Tabiat dan minat membaca di kalangan pelajar tingkatan empat di smk hulu kelang, gombak, selangor pada tahun 2010 - Tiew, Wai Sin (Persatuan Pustakawan Malaysia, 2010)
Using the survey methodology, this study explores the reading habits and interests of form four students from SMK Hulu Kelang, Gombak, Selangor. The results of the study revealed that 27 students (39.13%) spent one to two hours reading daily. The main source of reading material for 28 students (40.58%) is from the Internet. About 42.03% of the students buy the reading materials themselves and they primarily read for leisure (30.43%). A total of 47.83% read in the Malay language. The students themselves (52.17%) are their motivators for reading. The students (97.10%) are aware of the importance of reading and 57.97% agreed that the Nilam Programme, a nationwide reading programme run by the school, had succeeded in inculcating the reading habit in them.